Impact of environmental flow policy on power system balancing costs and river ecosystem service benefits - Juutinen, Artti; Virk, Z.; Huuki, H.; Ruokamo, E.; Kopsakangas-Savolainen, M.; Torabi Haghighi, A.; Marttila, H. (Elsevier, 2025)
Sustainable river regulations require more information on the costs and benefits of environmental flow constraints. This paper presents a case study focusing on the Nordic electricity market and ecosystem service situation. We impose tighter flow ramping constraints on a hydropower plant situated in the Kemijoki River and quantify the effects of the environmental flow policy on hydropower balancing services, river hydraulics and ecosystem services. Our findings reveal that as the environmental flow policy becomes more stringent, the optimal level of balancing market flexibility for the hydropower operator decreases. In addition, a hydrological flow analysis indicates that ecological improvements resulted from the policy. We compare the costs and benefits of the environmental flow policy. The findings indicate that the costs, hydropower revenue loss and increased system balancing costs are comparable to the willingness to pay for environmental improvements. If system balancing can be achieved without an increase in CO2 emissions, the willingness to pay for the improved river state increases, widening the gap between local benefits and system costs. The study insights can inform policymakers and private companies to better incorporate environmental concerns in the management of regulated rivers while acknowledging the value of hydropower in the power system.
Keywords: joet; virtaama; taloudelliset vaikutukset; ekosysteemipalvelut; sähkömarkkinat; kustannus-hyötyanalyysi; vesivoimalat; säätely; vesivoima; cost-benefit analysis; hydropeaking; environmental flow; balancing market; ecosystem services